2010
DOI: 10.1371/journal.pone.0010645
|View full text |Cite
|
Sign up to set email alerts
|

A Single Immunization with Soluble Recombinant Trimeric Hemagglutinin Protects Chickens against Highly Pathogenic Avian Influenza Virus H5N1

Abstract: BackgroundThe highly pathogenic avian influenza (HPAI) virus H5N1 causes multi-organ disease and death in poultry, resulting in significant economic losses in the poultry industry. In addition, it poses a major public health threat as it can be transmitted directly from infected poultry to humans with very high (60%) mortality rate. Effective vaccination against HPAI H5N1 would protect commercial poultry and would thus provide an important control measure by reducing the likelihood of bird-to-bird and bird-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
121
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(125 citation statements)
references
References 30 publications
3
121
1
Order By: Relevance
“…Together, these data indicate that nonadjuvanted sH5 3 antigen is able to elicit high titers of H5 cross-clade neutralizing antibody when administered using a prime/boost/boost regimen. Consistent with previous reports, 6,7,12 multiple immunizations of sH5 3 recombinant protein were required to generate consistently high neutralizing antibody titers.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…Together, these data indicate that nonadjuvanted sH5 3 antigen is able to elicit high titers of H5 cross-clade neutralizing antibody when administered using a prime/boost/boost regimen. Consistent with previous reports, 6,7,12 multiple immunizations of sH5 3 recombinant protein were required to generate consistently high neutralizing antibody titers.…”
supporting
confidence: 90%
“…4 Recent studies demonstrated that rHA engineered to form a stable trimeric configuration elicited a protective immune response in vaccinated animals. [5][6][7][8][9][10] Neutralizing antibody levels and protection from disease were enhanced in mice vaccinated with soluble rHA trimers as compared to animals vaccinated with rHA monomers, 5,8 indicating the importance of immunogens that mimic those expressed by the infectious agent. Along these lines, the composition and/or number of N-linked glycans on rHA trimers have been shown to modify the level of the protective antibody response.…”
Section: Ross Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Stimune, also known as Specol, has been used successfully in an i.m. vaccine using soluble trimeric H5 protein in chicken (Cornelissen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%